2014
DOI: 10.1007/s12223-014-0335-1
|View full text |Cite
|
Sign up to set email alerts
|

The adenylyl cyclase Rv2212 modifies the proteome and infectivity of Mycobacterium bovis BCG

Abstract: All organisms have the capacity to sense and respond to environmental changes. These signals often involve the use of second messengers such as cyclic adenosine monophosphate (cAMP). This second messenger is widely distributed among organisms and coordinates gene expression related with pathogenesis, virulence, and environmental adaptation. Genomic analysis in Mycobacterium tuberculosis has identified 16 adenylyl cyclases (AC) and one phosphodiesterase, which produce and degrade cAMP, respectively. To date, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…Similar results have also been reported earlier for Eis protein, a thermostable aminoglycoside acetyltransferase, which enhances the survival of Mycobacterium within macrophages (13,31). A recent report by Pedroza-Roldan et al (17) has also shown that the overexpression of Rv2212 caused the enhanced replication and survival of Mycobacterium bovis BCG Pasteur 1173P2.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have also been reported earlier for Eis protein, a thermostable aminoglycoside acetyltransferase, which enhances the survival of Mycobacterium within macrophages (13,31). A recent report by Pedroza-Roldan et al (17) has also shown that the overexpression of Rv2212 caused the enhanced replication and survival of Mycobacterium bovis BCG Pasteur 1173P2.…”
Section: Discussionsupporting
confidence: 87%
“…Rv2212 is known to be regulated by fatty acids and operates as an ATP sensor by integrating the signals sensing fatty acids and intracellular pH with the cAMP as the output (14). Rv2212 is also shown to modify the proteome and infectivity of Mycobacterium bovis BCG (17).…”
Section: Discussionmentioning
confidence: 99%
“…This latter result is in a sharp contrast with observation by Pedroza-Roldán et al ( 2015 ) concerning the BCG-Rv2212 strain, which exhibited almost identical growth with control strain in mouse organs. We suspect that this difference may be connected with different locations of Mtb and M. bovis BCG within the host cells.…”
Section: Discussioncontrasting
confidence: 98%
“…As shown earlier, M. bovis BCG with overexpressed Rv2212 did not show a significant difference in growth in vitro compared to the wild type bacteria; however, only high initial cell concentrations were used in this study. Remarkably, this strain displayed a substantial growth acceleration compared to the control strain within mouse macrophages, i.e., when stressful conditions for intracellular parasite are evident (Pedroza-Roldán et al, 2015 ). Similarly, the overexpression of Rv2212 in M. smegmatis resulted in an enhanced survival of bacteria within macrophages (Ganaie et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…Bovis enhances the survival of recombinant strain in murine macrophages (Pedroza-Roldan et al, 2015). Bioinformatic analysis study was found that cAMP receptor protein (CRP) regulated genes were conserved in pathogenic mycobacteria, and suggested that CRP regulated genes may play a role in the pathogenesis of mycobacteria (Akhter et al, 2008).…”
Section: Mycobacterium Tuberculosis Rv1265 Promotes Mycobacterial Intmentioning
confidence: 99%